2009
DOI: 10.1038/sj.bjc.6605484
|View full text |Cite
|
Sign up to set email alerts
|

Birth characteristics and the risk of childhood rhabdomyosarcoma based on histological subtype

Abstract: BACKGROUND: Little is known about risk factors for childhood rhabdomyosarcoma (RMS) and the histology-specific details are rare. METHODS: Case -control studies formed by linking cancer and birth registries of California, Minnesota, New York, Texas and Washington, which included 583 RMS cases (363 embryonal and 85 alveolar RMS) and 57 966 randomly selected control subjects, were analysed using logistic regression. The associations of RMS (overall, and based on embryonal or alveolar histology) with birth weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 39 publications
2
37
1
Order By: Relevance
“…Increased risk of RMS has also been associated with various clinical factors or environmental exposures, including in utero x-ray exposure and accelerated in utero growth [6,7]. However, some of these associations were reported in small to moderate size casecontrol studies and have not been validated in larger epidemiologic studies.…”
Section: Epidemiologymentioning
confidence: 95%
“…Increased risk of RMS has also been associated with various clinical factors or environmental exposures, including in utero x-ray exposure and accelerated in utero growth [6,7]. However, some of these associations were reported in small to moderate size casecontrol studies and have not been validated in larger epidemiologic studies.…”
Section: Epidemiologymentioning
confidence: 95%
“…In addition, several studies have evaluated birth characteristics and childhood rhabdomyosarcoma and suggest that increased birth weight [20], increased maternal age [13, 2022], increased paternal age [20, 22], being born large for gestational age [20], and late or lack of prenatal care [22] are associated with an increased risk of childhood rhabdomyosarcoma. Similar to other childhood cancers, high birth order (3+) is suggested to have a protective effect on childhood rhabdomyosarcoma [9, 20]. A previous report indicated that being born as a twin or a multiple may be associated with higher risk of childhood rhabdomyosarcoma, but this finding was not statistically significant [22].…”
Section: Introductionmentioning
confidence: 99%
“…The largest studies evaluating the association of birth characteristics and childhood rhabdomyosarcoma to date have primarily relied on a large dataset consisting of a pool of cancer registry data linked to birth records from five states across the United States [9, 13, 18, 20, 25]. This pooled dataset has provided sufficient statistical power to assess potential risk factors for rare childhood cancer types, and often their histologic subtypes; however, linkage studies may be subject to selection bias, as children who are born and diagnosed in separate states due to residential mobility are often excluded.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mothers delivering macrosomic fetuses are at an increased risk of experiencing prolonged labor, C-section, abnormal hemorrhage and perineal laceration (4,5). Numerous studies have indicated that high birth weight is associated with long-term health risks for the newborn, including an increased risk of obesity, diabetes and certain types of cancer (6)(7)(8)(9). In the past two to three decades, the incidence of macrosomia in developed countries has increased by 15-25% (2).…”
Section: Introductionmentioning
confidence: 99%